PATTERNS OF HOMICIDAL DEATH CASES IN BHAVNAGAR REGION OF GUJARAT (Journal of Forensic Medicine & Toxicology, 2013)
Current prospective study was undertaken at Mortuary Complex of Sir Takhtsinhji General Hospital, Bhavnagar, Gujarat to study trends of homicidal death cases in Bhavnagar region. Among 2256 medicolegal postmortem cases during period of June-2008 to Aug 2011, 70 cases of homicide were selected as per inclusion exclusion criteria and studied. Homicide incidence rate from 2009 to 2011 was seen to be increased in Bhavnagar region. Observations of present study showed similarities with most of the observations of previous similar study by other authors. Socioeconomic profile, education, regional sociocultural environment, family type, sex, marital status, and age of victim are strongly associated with homicidal incidence. Site of incidence, availability of weapon, motive or reason behind incidence, method of assault and patterns of mechanical injuries are interrelated in homicidal incidences. Favorable combination of these parameters produces favorable circumstances for homicidal incidence. Modification of such parameters is ultimate answer to curtail violence.
Keywords: Homicidal deaths; Patterns; Parameters; Forensic aspects